Institutional arrangements in the commercialization of electric energy from sugarcane biomass in the Brazilian midwest - da Silva Garcia, Marli; Vilpoux, Olivier François; Cereda, Marney Pascoli [UNESP] (FapUNIFESP (SciELO), 2021)
Reducing the use of fossil fuels and mitigating environmental impacts justifies the generation of electricity from renewable sources. In Brazil, sugarcane is the biomass that most generates electricity, and Mato Grosso do Sul state accounts for 10% of this electricity. Production can be traded in the spot market, long-term contracts regulated by the Federal Government, or free contracts between companies. Despite these options, only half of the sugarcane industries in Mato Grosso do Sul commercialize electricity. Based on Transaction cost economics, the objective of this work is to identify the most suitable governance structures used in the commercialization of electricity produced by the sugarcane plants in the state of Mato Grosso do Sul and to evaluate the institutional environment impact on these structures. A questionnaire was applied to all sugarcane companies in the state, and interviews were conducted with specialists and regulatory agencies. The results indicate that the widespread use of plural forms of governance for the commercialization of energy reduces the risks linked to a weak institutional environment and judicialization of the spot market. The preference for free contracts and a large number of short-term transactions indicate a lack of trust in the existing institutions, with the need to strengthen independent regulatory agencies.
Arranjos institucionais na comercialização de energia elétrica de biomassa de cana-de-açúcar na região centro-oeste do Brasil
Keywords: economia dos custos de transação; energia renovável; formas plurais; instituições; institutions; plural forms; renewable energy; transaction cost economics